The Position Of Indonesia In Asean Economic Community 2015 - Afgan Fadilla (Institute of Computer Science (IOCS), 2019)
This research is motivated by the challenges faced by Indonesia on the establishment of the AEC (ASEAN Economic Community) that has a basic concept in the form of trade liberalization. The challenge is to be reduced sovereignty with the indicator decreasing authority of the state in regulating economic policy. Researchers dissect this problem by using the theory of realism that can be seen suitability Indonesian position with the theory used. This research uses qualitative research with an interpretive case study approach. The technique of collecting data is library research by collecting secondary data were then analyzed using qualitative techniques. Results of the research is Indonesia's position in the MEA discrepancy with the theory of realism regarding the challenge. The conclusions in this study is Indonesia as a country has experienced a reduction in its authority to regulate its own policies in harmony with the sovereignty of Indonesia as a state. Aside from being one of the member countries in ASEAN, Indonesia is also a country that the largest predicated in the Southeast Asia region and should not be handing sovereignty over the country's interests abroad.